Actinomycetes from Plant Rhizosphere in Gorontalo Karst Area as Plant Growth Promoting Rhizobacteria - Citra Leonita Matalauni; Yuliana Retnowati; Abubakar Sidik Katili; Novri Youla Kandowangko; Ani M. Hasan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aimed to describe Actinomycetes from the rhizosphere of plants in the Gorontalo karst area as Plant Growth Promoting Rhizobacteria (PGPR). The research method is based on a quantitative descriptive method. Soil samples from the rhizosphere were collected using a purposive sampling technique from 8 plant species at two locations in the Gorontalo karst region, namely the Tanjung Kramat Hills. The characteristics of PGPR in this study focused on phosphate solubilization ability, Indole Acetic Acid (IAA) production, antagonism against the fungus Fusarium oxysporum, and tolerance to fungicides. Potential PGPR isolates were analyzed for phylogenetic relationships based on 16S rRNA gene sequences. The results showed that there were 6 actinomycetes isolates (RzHKC-01, RzKO-02, RzO-03, RzAK-04, RzPK-05, and RzOC-06) from 8 plant species in the Gorontalo karst region. One actinomycetes isolate, RzPK-05, showed potential as a PGPR with the ability to solubilize phosphate and produce IAA at 0.165 mg/L and 0.133 mg/L, respectively. Isolate RzPK-05 exhibited antagonistic properties against Fusarium oxysporum with an inhibition rate of 82.24% and was tolerant to fungicides such as Captive, Benlate, and Thiramo up to a concentration of 100 mg/L. Molecular analysis based on the 16S rRNA gene and phylogenetic tree reconstruction indicated that the RzPK-05 isolate is closely related to the genus Streptomyces with 100% similarity.